Short term effects of maternal obesity on mother and fetus: a prospective study - Thota, Amrutha R.; Bhandiwad, Ambarisha; Sakhireddy, Vineet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Obesity is such a common health care problem of female population that have major impact on pregnancy. The worldwide prevalence of obesity is more than doubled in between 1980 and 2015. The objectives of present study are to observe whether obese women have an increased risk of pregnancy related complications and adverse fetal outcome and also to compare pregnancy outcomes in different classes of BMI in obese group. Methods: A prospective observational study conducted in OBG department JSS Hospital, Mysore from November 2014 to July 2016. All pregnant women attending OPD and inpatients of antenatal wards were screened for pre-pregnancy BMI. Total number of singleton births were 5727 in our institution. Out of which 314 obese pregnant women were included in the study group, remaining 5413 non-obese pregnant mothers were taken as control group respectively. They are closely monitored in every antenatal visit for development of complications such as pre-eclampsia, gestational diabetes mellitus, increased rate of caesarean section and presence of macrosomia (B.wt >3.5kg). Results: In comparison to normal BMI pregnant women, obese mothers had an increased risk of gestational hypertension (16.9% versus 2.0%, OR-2.3) gestational diabetes mellitus (35.7% versus 3.1%, OR-2.84), preeclampsia (23.9% versus 5%,0R-1.64) cesarean sections (75.2% versus 65.4%), macrosomia (45.9% versus 22%, OR-1.64), it was also found that as BMI increases the incidence of these complications increase as seen in different classes of obese population. Conclusions: Pregnancy associated with obesity is considered as a high-risk pregnancy and obesity being a modifiable risk factor, educating women in early pregnancy and preconceptional counseling regarding harmful effects of obesity and information regarding appropriate gestational weight gain is essential.